Analysis of Determination of Depositional Environment of Cinambo Formation Sandstone Member Based on Distribution of Planktonic and Benthonic Foraminifera in Sumedang Area, West Java - Ahmad Thoriq Rabbani Al Ula; Edy Sutriyono; Ugi Kurnia Gusti (Westscience Press, 2026)
Micropaleontological analysis is an important method in determining the relative age and depositional environment of sedimentary rocks through the identification of planktonic and benthonic foraminifera as indicators of marine paleo-environments. This study aims to determine the bathymetric environment of the Cinambo Formation Sandstone Member in the Jatigede area and its surroundings, Sumedang Regency, based on the distribution of foraminifera, determine the relative age of the rocks, and interpret the depositional environment and sedimentation dynamics. The research methods include sampling at two outcrop locations, preparation using H₂O₂, multistage sieving, and microscopic identification of foraminifera. The determination of the relative age was carried out based on the Blow (1969) classification, while the interpretation of the bathymetric environment refers to Barker (1960). The results of the analysis show the presence of planktonic fossils such as Orphanage all over the world, Transitional Praeorbulina, And Globigerina praebulloides which indicates a relative age of N8 – N9 or Early Miocene to Middle Miocene, while benthonic fossils such as Fissurina wieneri, Osangularia bangalensis, and Alveolophragmium scitulumindicates an upper bathyal depositional environment. Based on these data, the Cinambo Formation Sandstone Member was deposited in a marine environment in the lower to middle fan section (lower – middle fan) through the turbidite gravity flow mechanism, reflecting transgressive conditions during the Miocene in the Jatigede area.